Leadership and Trust - Hassan, Arif (2012)
Leadership is an influence process. It means leaving a mark on others. It is initiating and guiding others and the result is change. The product is new character or direction that otherwise would never be. Trust is based on the belief that one will not behave opportunistically and is defined as “a psychological state comprising the intention to accept vulnerability based upon positive expectation of the intentions and behavior of another.” (Rousseau, Sitkin, Burt & Camerer, 1998, p.395). Trust is the building block of social exchange and role relationship. Leader member relationship needs trust. It is impossible to lead people who do not trust you. Trust in leader has been found to influence employees work commitment, intention to stay in the organization, organizational citizenship behavior, quality of communication, and decision making. Unfortunately, growing number of scandals and resultant corporate failures, as well as reengineering and downsizing is seriously eroding employees trust in their leaders. The paper examines the nature of trust and its relationship with organizational leadership. Further it suggests ways through which trust can be promoted in organizations.